EXPLORING THE EFL STUDENTS’ INTEREST ON ACADEMIC READING - Alimin Alimin; Sairotul Khabibillah; Happy Kusuma Wardani (STKIP PGRI Jombang, 2023)
This study aims to explore the interest of EFL students in academic reading and the factors influencing their interest. The design employed a descriptive qualitative approach. The data were obtained from twenty-four students in the third semester of the English Education study program at Qomaruddin University. The data for this study were collected through questionnaires and interviews. The questionnaire aimed to determine the students' interest in reading, while the interview aimed to gather data on the factors influencing students' interest. The results of the study were presented using descriptive qualitative analysis. The results of this study showed that 68% of students responded that they rarely read, and 75% of students prefer watching TV to academic reading. Several factors influenced students' interest in reading including awareness, motivation, and environment.